VD_FINDINFO Arrêt / 2010 / 1301 vom 12. August 2010 - VD Tribunal cantonal (2010)
PRESTATION D'ASSURANCEAI, COMPENSATIO, SURASSURANCE, AVANCEEN GÉNÉRAL | 1 LAI, 69 LAI, 83 LOJV, 22 LPGA, 57 LPGA, 61 let. a LPGA, 61 let. g LPGA, 69 LPGA, 85bis RAI, 2 LPA-VD, 55 al. 1 LPA-VD, 93 al. 1 let. a LPA-VD, 94 al. 1 let. a LPA-VD